Gloss to the judgment of the District Court in Słupsk of 20 October 2020, V U 198/19 (not published) - Lewandowski, Piotr (Studia Iuridica Toruniensia, 2021)
The subject of the judgement with commentaries is the issue of effectiveness of pension benefits’ lowering to officers of special forces. The court has stated that such a lowering based on the revised pension act of 2016 is ineffective due to lack of evidence for individual acts taken in violation of the law and human rights. In this respect the court referred to a resolution of the Supreme Court of 16 September 2020 and restored pension benefits as granted before 1 October 2017 excluding regulations of the revised pension act of 2016.